Pathogens and Molds Affecting Production and Quality of Cannabis sativa L. - Punja, Zamir K.; Collyer, Danielle; Scott, Cameron; Lung, Samantha; Holmes, Janesse; Sutton, Darren (Frontiers in Plant Science, 2019)
Plant pathogens infecting marijuana (Cannabis sativa L.) plants reduce growth of the crop by affecting the roots, crown, and foliage. In addition, fungi (molds) that colonize the inflorescences (buds) during development or after harvest, and which colonize internal tissues as endophytes, can reduce product quality. The pathogens and molds that affect C. sativa grown hydroponically indoors (in environmentally controlled growth rooms and greenhouses) and field-grown plants were studied over multiple years of sampling. A PCR-based assay using primers for the internal transcribed spacer region (ITS) of ribosomal DNA confirmed identity of the cultures. Root-infecting pathogens included Fusarium oxysporum, Fusarium solani, Fusarium brachygibbosum, Pythium dissotocum, Pythium myriotylum, and Pythium aphanidermatum, which caused root browning, discoloration of the crown and pith tissues, stunting and yellowing of plants, and in some instances, plant death. On the foliage, powdery mildew, caused by Golovinomyces cichoracearum, was the major pathogen observed. On inflorescences, Penicillium bud rot (caused by Penicillium olsonii and Penicillium copticola), Botrytis bud rot (Botrytis cinerea), and Fusarium bud rot (F. solani, F. oxysporum) were present to varying extents. Endophytic fungi present in crown, stem, and petiole tissues included soil-colonizing and cellulolytic fungi, such as species of Chaetomium, Trametes, Trichoderma, Penicillium, and Fusarium. Analysis of air samples in indoor growing environments revealed that species of Penicillium, Cladosporium, Aspergillus, Fusarium, Beauveria, and Trichoderma were present. The latter two species were the result of the application of biocontrol products for control of insects and diseases, respectively. Fungal communities present in unpasteurized coconut (coco) fiber growing medium are potential sources of mold contamination on cannabis plants. Swabs taken from greenhouse-grown and indoor buds pre- and post-harvest revealed the presence of Cladosporium and up to five species of Penicillium, as well as low levels of Alternaria species. Mechanical trimming of buds caused an increase in the frequency of Penicillium species, presumably by providing entry points through wounds or spreading endophytes from pith tissues. Aerial distribution of pathogen inoculum and mold spores and dissemination through vegetative propagation are important methods of spread, and entry through wound sites on roots, stems, and bud tissues facilitates pathogen establishment on cannabis plants.